Place of imidazoline receptor agonists in the treatment of hypertension - D. V. Nebieridze; A. S. Safaryan (Кардиоваскулярная терапия и профилактика)
The review is devoted to selective I1-imidazoline-receptor agonists. An analysis of Russian and foreign studies is presented, the results of which indicate that this drug class not only provides adequate and long-term control of blood pressure, but also has a number of favorable metabolic effects. Therefore, it contributes to reducing insulin resistance (weight loss) and has organ protective properties (endothelial function improvement, left ventricular hypertrophy regression, microalbuminuria reduction). At the same time, selective I1-imidazoline-receptor agonists are much less likely to cause side effects characteristic of old-generation sympatholytic agents. This class of drugs is invariably included in Russian guidelines for the diagnosis and treatment of hypertension.